Relative risk of the COVID-19 pandemic and regional inflation convergence in Indonesia - Sayifullah, Sayifullah; Arifin, Samsul (Department of Accounting, Faculty of Business, Universitas PGRI Yogyakarta, 2023)
This study investigates the relationship between the risk of a COVID-19 pandemic and the regional inflation convergence in Indonesia. It is important to examine the regional inflation convergences to evaluate the inflation rate and the impact of macroeconomic policy on inflation convergence, as the COVID-19 recession differs from the previous inflation recession. To calculate the impact of the relative risk of the COVID-19 pandemic on regional inflation convergence in Indonesia, the dynamic econometric spatial panel data model is used to calculate relative risk without spatial or SIRs. On the contrary, for calculating the risk relative to spatial elements, the CAR Leroux or BSCL Bayesian Spatial Model is used. Using BSCL, the calculation of the relative risk value for the COVID-19 pandemic concludes that Sumatera Island, Java Island, Kalimantan Island, Sulawesi Island, Maluku Island, and Papua Island have high risks, while Bali Island and Nusa Tenggara Island have low risks. In both static and dynamic models, the influence of currency circulation on inflation convergence is positive, and the relative risk of a COVID-19 pandemic on inflation convergence is negative. Studies show that the COVID-19 pandemic is a deterrent to inflation convergence, while the circulation of money drives inflation convergence.